Kunst als Spiegel realer, virtueller und imaginärer Welten Zum künstlerischen Schaffen Olga Neuwirths - Drees, Stefan; Kogler, Susanne (Fokus Musik. Musikwissenschaftliche Beiträge der Kunstuniversität Graz, 2020)
Olga Neuwirth's works are characterised by socio-political statements and great artistic openness. With installations, videos, operas, theatre music, films, vocal, instrumental and electronic music, she serves a wealth of genres whose boundaries are constantly being expanded and transcended. From Neuwirth's earliest works onwards, film, video, electronics and installation elements have found their way into genres such as chamber music, oratorio and opera. Neuwirth's works call for an examination of identity and memory, stability and processuality as well as utopia and dystopia. Many current aesthetic and philosophical discussions are thus reflected in her artistic work. The contributions in this volume aim to illuminate the artist's oeuvre in all its complexity and richness of relationships and to explore different - intermedial, music-historical and socio-critical - contexts.